Prediction of reading and writing difficulties of first graders using dyslexia risk questionnaire (DRQ) in preschool age - Labanienė, Katažyna; Gedutienė, Reda; Gintilienė, Gražina (Special Education, 2019)
This article examines relationships between the scores of Dyslexia Risk Questionnaire (DRQ) in preschool age and the abilities, necessary for acquisition of reading and writing skills, as well as reading and writing skills in the 1st Grade. The results of the study showed that the scores of Dyslexia Risk Questionnaire (DRQ), completed by pre-primary teachers and parents of children attending pre-primary group, are related to prognostic indicators of reading and writing difficulties (phonological abilities: rapid naming, phonological awareness, short-term auditory memory; vocabulary; visual-motor skills), as well as to 1st graders’ reading skills and their reading and writing ratings provided by parents and teachers.